2002
DOI: 10.1002/cncr.10782
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of paclitaxel plus carboplatin in patients with advanced carcinoma of the urothelium and renal dysfunction (E2896)

Abstract: BACKGROUNDChemotherapy options for the patients with advanced urothelial carcinoma and renal dysfunction are limited. The authors performed a Phase II trial of paclitaxel plus carboplatin in patients with advanced carcinoma of the urothelium and renal dysfunction.METHODSForty‐two patients were accrued; 37 eligible patients were treated. Patients received paclitaxel 225 mg/m2 over three hours followed by carboplatin targeted area under the concentration‐time curve = 6 mg/mL · minute every three weeks for up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(24 citation statements)
references
References 14 publications
1
22
0
1
Order By: Relevance
“…Other combinations with paclitaxel, oxaliplatin or epirubicin have shown some effectivity in small phase II trials [39][40][41].…”
Section: Systemic Therapy Of Muscle Invasive or Metastatic Bladder Camentioning
confidence: 99%
“…Other combinations with paclitaxel, oxaliplatin or epirubicin have shown some effectivity in small phase II trials [39][40][41].…”
Section: Systemic Therapy Of Muscle Invasive or Metastatic Bladder Camentioning
confidence: 99%
“…Several phase II trials have shown that newer drugs, such as paclitaxel and docetaxel, have potential as single agents or in combination in the treatment of metastatic urethelial cancer [30][31][32][33]. Carboplatin has also been tested in patients with renal dysfunction [31,32].…”
Section: New Chemotherapeutic Agentsmentioning
confidence: 99%
“…The dose of paclitaxel recommended for phase II study was 225 mg/m 2 . Subsequently, several phase II trials have been performed with varying doses of paclitaxel (150-225 mg/ m 2 ) and carboplatin (AUC 5-6) reporting overall response rates of 14%-65%, with complete responses in 0%-40% [16][17][18][19][20][21]. This regimen has proven well tolerated with predominantly mild hematologic and neurologic toxicities.…”
Section: Paclitaxel Plus Carboplatinmentioning
confidence: 99%